Agroforestry-Based Land Rehabilitation in KHDTK UGM: Integration of Multipurpose Species and Renewable Energy Crops - Fitra K Tegar; Louis B. R. Wijanarto; Muhammad A. Noor; Lutfiyyah Roihanah; Angelina N.; Helga Monica; Hermudananto Hermudananto (School of Postgraduate Studies, Diponegoro Univer, 2026)
There is currently a problem of land degradation in Indonesia, requiring the rehabilitation of over 12.7 million hectares. Agroforestry has been considered one of the most effective strategies for restoring ecological functions while providing socio-economic benefits to local people. The purpose of this study was to develop an agroforestry-based land rehabilitation strategy for Compartment 5 of KHDTK at Universitas Gadjah Mada, located in Ngawi Regency, East Java, Indonesia, using the CASM model. This study involved assessing both biophysical and socio-institutional aspects in April 2025. Three Land Management Units (LMUs) were identified using the spatial overlay analysis of soil type, slope, rainfall, and land cover. The fieldwork was conducted across 18 plots of land, while socio-economic and property rights issues were collected through semi-structured interviews with locals. The findings indicated that LMU 1 was assigned to Class III Land Capability. However, LMUs 2 and 3 were assigned to Class IV, indicating severe soil limitations due to shallow soil depth, clayey soil, and susceptibility to erosion. Analysis of suitability indicated that Calliandra calothyrsus and Arenga pinnata had marginal suitability (S3) across all three land management units. In contrast, Calophyllum inophyllum adapted better to local conditions and faced fewer soil and climatic limitations. The availability and manageability assessment identified problems with informal land use, inactive local institutions, and poor coordination among stakeholders. These factors allowed for the identification of potential for joint efforts in land rehabilitation through cooperation with KHDTK UGM and other parties. The research results indicate that an agroforestry system based on the cultivation of multipurpose tree species and renewable energy crops has great potential in land rehabilitation planning in KHDTK UGM. A pilot project is suggested.